EFEKTIVITAS PENGGUNAAN SOSIAL MEDIA DALAM MENINGKATKAN KESADARAN MEREK DI PT PUPUK SRIWIDJAJA PALEMBANG - Voni Karnelia; Sabeli Aliya (Bajang Institute, 2024)
How effective is the use of social media in increasing community or customer engagement, with fairly active interactions, such as likes, comments, and sharing information. The purpose of this study is to investigate and explore in depth about how the effectiveness of using social media in increasing brand awareness. The purpose of this study is to contribute to the development of theoretical knowledge in digital marketing for readers or writers, this research is a qualitative study with the observation method, data obtained from direct observation at the internship site which is then recorded or recorded directly. The data collected shows that PT Pupuk Sriwidjaja is active on various social media platforms such as TikTok and Instagram. Content posting is done with varying frequency depending on the platform. The published content is diverse, including images, videos, and articles. Customer responses show positive interactions, such as likes, comments, and shares.Based on the research that has been conducted, it can be concluded that PT Pupuk Sriwidjaja Palembang has successfully utilized digital technology well to increase brand awareness of their products. They use various digital platforms and channels, such as social media, websites, and online advertising, to achieve brand awareness.